Understanding Cancer : A Patient's Guide to Diagnosis, Prognosis, and Treatment - Coleman, C. Norman (Book collections on Project MUSE., 2006)
In this edition, Dr. Coleman describes new treatments that target specific types of cancer as well as treatments that are designed for a particular individual. He also discusses the era of molecular medicine, including biomarkers, novel imaging, molecular signatures and profiling, and molecular-targeted therapy. Some of these therapies are only available through a clinical trial, therefore, Dr. Coleman includes a detailed discussion of what is involved in participating in research trials.